Effects of Expectancy on Cognitive Performance, Mood, and Psychophysiology in Healthy Adolescents and Their Parents in an Experimental Study - Watolla, Daniel; Mazurak, Nazar; Gruss, Sascha; Gulewitsch, Marco D.; Schwille-Kiuntke, Juliane; Sauer, Helene; Enck, Paul; Weimer, Katja (Frontiers in Psychiatry, 2020)
Objective: Placebo effects on cognitive performance and mood and their underlying mechanisms have rarely been investigated in adolescents. Therefore, the following hypotheses were investigated with an experimental paradigm: (1) placebo effects could be larger in adolescents than in adults, (2) parents’ expectations influence their adolescents’ expectations and placebo effects, and (3) a decrease in stress levels could be an underlying mechanism of placebo effects. Methods: Twenty-six healthy adolescents (13.8 ± 1.6 years, 14 girls) each with a parent (45.5 ± 4.2 years, 17 mothers) took part in an experimental within-subjects study. On two occasions, a transdermal patch was applied to their hips and they received an envelope containing either the information that it is a Ginkgo patch to improve cognitive performance and mood, or it is an inactive placebo patch, in counterbalanced order. Cognitive performance and mood were assessed with a parametric Go/No-Go task (PGNG), a modification of California Verbal Learning Test, and Profile of Mood Scales (POMS). Subjects rated their expectations about Ginkgo’s effects before patch application as well as their subjective assessment of its effects after the tests. An electrocardiogram and skin conductance levels were recorded and root mean squared successive differences (RMSSD), high frequency power (HF), and the area under the curve of the SCL (AUC) were analyzed as psychophysiological stress markers. Results: Expectations did not differ between adolescents and parents and were correlated concerning reaction times only. Overall, expectations did not influence placebo effects. There was only one significant placebo effect on the percentage of correct inhibited trials in one level of the PGNG in adolescents, but not in parents. RMSSD and HF significantly increased, and AUC decreased from pre to post patch application in adolescents, but not in parents. Conclusion: With this experimental paradigm, we could not induce relevant placebo effects in adolescents and parents. This could be due to aspects of the study design such as application form and substance, and that healthy subjects were employed. Nevertheless, we could show that adolescents are more sensitive to psychophysiological reactions related with interventions which could be part of the underlying mechanisms of placebo effects in adolescents.